Characteristics of people with recurrent ankle sprains: a systematic review with meta-analysis. Issue 8 (21st January 2011) - Hiller, Claire E; Nightingale, Elizabeth J; Lin, Chung-Wei Christine; Coughlan, Garrett F; Caulfield, Brian; Delahunt, Eamonn
Abstract : Objective: To examine whether people with recurrent ankle sprain, have specific physical and sensorimotor deficits. Design: A systematic review of journal articles in English using electronic databases to September 2009. Included articles compared physical or sensorimotor measures in people with recurrent (≥2) ankle sprains and uninjured controls. Main outcome groups: Outcome measures were grouped into: physical characteristics, strength, postural stability, proprioception, response to perturbation, biomechanics and functional tests. A meta-analysis was undertaken where comparable results within an outcome group were inconsistent. Results: Fifty-five articles met the inclusion criteria. Compared with healthy controls, people with recurrent sprains demonstrated radiographic changes in the talus, changes in foot position during gait and prolonged time to stabilisation after a jump. There were no differences in ankle range of motion or functional test performance. Pooled results showed greater postural sway when standing with eyes closed (SMD=0.9, 95% CI 0.4 to 1.4) or on unstable surfaces (0.5, 0.1 to 1.0) and decreased concentric inversion strength (1.1, 0.2 to 2.1) but no difference in evertor strength, inversion joint position sense or peroneal latency in response to a perturbation. Conclusion: There are specific impairments in people with recurrent ankle sprain but not necessarily in areas commonly investigated.